Pseudomonas pelvic osteomyelitis in a healthy child - Nour Akhras; Alexander Blackwood (MDPI AG, 2011)
Pediatric pelvic osteomyelitis is a rare entity. The diagnosis is frequently delayed due to difficulty in confirming the diagnosis. To our knowledge, this is the first case report of Pseudomonas pelvic osteomyelitis in a previously healthy adolescent boy. The diagnosis was made radiographically and confirmed by culture. The patient was treated with Levofloxacin and Gentamicin resulting in a complete recovery.